Everyday Reconciliation in Post-Khmer Rouge Cambodia Subtle Agency and Hidden Narratives - Lee, SungYong (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines the nature of everyday peace mobilised in post-conflict settings. It specifically aims to examine the reconstruction of relationships between local communities and former Khmer Rouge leaders in Cambodia, using social reconciliation as an indicator of peace. Based on the empirical examination, this study will reveal key features of everyday peace like plurality, connectivity and subtlety, and local communities' agency for peacebuilding. Research questions that will be examined include what does everyday peace look like? What forms of everyday practice have community members developed and utilised? How is the local process for relationship building related to the wider peacebuilding and governance contexts in the country? And how have community members handled and destabilised the mainstream narratives related to the Khmer Rouge in the process? The volume will present new conceptual and theoretical innovations relevant to the central debates on everyday peace, with an empirical examination of Cambodia. SungYong Lee is Associate Professor at the National Centre for Peace and Conflict Studies, University of Otago, New Zealand. His research expertise is on peacebuilding and post-conflict reconstruction. His recent books include Multi-level Reconciliation and Peacebuilding (with Kevin Clements, 2021), Local Ownership in Asian Peacebuilding: Development of Local Peacebuilding Models (2019), and International Peacebuilding: An Introduction (with Alpaslan Özerdem, 2016).
Chapter 1. Introduction -- Chapter 2. Dealing with the Khmer Rouge History in Cambodia -- Chapter 3. Promotion of Everyday Reconciliations -- Chapter 4. Commonality and Plurality of Everyday Practice -- Chapter 5. Mundaneness and Subtlety -- Chapter 6. Connection to Wider Contexts -- Chapter 7. Disrupting the Mainstream Narratives -- Chapter 8. Conclusion.
Keywords: Peace; Political science; Peace and Conflict Studies; Politics and International Studies